Re-branding Produk UMKM Desa Suling Wetan Melalui Logo Baru dengan Sistem Digital Marketing - Sundahri; Rahman, Difany Aulia; Widyaningsih, Windi; Sianipar, Novika Aliza; Hendriana, Fezira Rosa; Ayumasita, Karomitafitri; Gunawan, Vito Chandra; Hasanah, Hepniatul; Jazimah, Hilda Nurwakidah (Jurnal Pengabdian Magister Pendidikan IPA, 2023)
In the midst of rapid technological development and internet utilization, the business world has undergone changes, one of which is MSMEs in Suling Wetan Village. There are several MSMEs in the village, such as tempeh chips, crispy intestines, and mushrooms. The problem of MSMEs in Suling Wetan Village is the lack of ability in product management and marketing. This causes MSME products in Suling Wetan Village to be less well known, especially in the area itself. The purpose of this work program is to develop village MSMEs, especially Suling Wetan Village, through a new logo with a digital marketing system to be better known and get the attention of the market sector in selling products more widely.